Damage Trajectories in Systemic Sclerosis Using Group‐Based Trajectory Modeling. Issue 3 (15th November 2022) - Barbacki, Ariane; Baron, Murray; Wang, Mianbo; Zhang, Yuqing; Stevens, Wendy; Sahhar, Joanne; Proudman, Susanna; Nikpour, Mandana; Man, Ada; ,
Abstract : Objective: Systemic sclerosis (SSc) is an autoimmune disease characterized by progressive organ damage, which can be measured using the Scleroderma Clinical Trials Consortium Damage Index (SCTC‐DI). We aimed to identify whether distinct trajectories of damage accrual exist and to determine which variables are associated with different trajectory groups. Methods: Incident cases of SSc (<2 years) were identified in the Australian Scleroderma Interest Group and Canadian Scleroderma Research Group prospective registries. Group‐based trajectory modeling was used to identify SCTC‐DI trajectories over the cohort's first 5 annual visits. Baseline variables associated with trajectory membership in a univariate analysis were examined in multivariable models. Results: A total of 410 patients were included. Three trajectory groups were identified: low (54.6%), medium (36.2%), and high (10.3%) damage. Patients with faster damage accrual had higher baseline SCTC‐DI scores. Older age (odds ratio [OR] 1.57 [95% confidence interval (95% CI) 1.18–2.10]), male sex (OR 2.55 [95% CI 1.10–5.88]), diffuse disease (OR 6.7 [95% CI 2.57–17.48]), tendon friction rubs (OR 5.4 [95% CI 1.86–15.66]), and elevated C‐reactive protein level (OR 1.98 [95% CI 1.49–2.63]) increased the odds of being in the high‐damage group versus the reference (low damage), whereas White ethnicity (OR 0.31 [95% CI 0.12–0.75]) and anticentromere antibodies (OR 0.24 [95% CI 0.07–0.77]) decreased the odds. Conclusion: We identified 3 trajectories of damage accrual in a combined incident SSc cohort. Several characteristics increased the odds of belonging to worse trajectories. These findings may be helpful in recognizing patients in whom early aggressive treatment is necessary.